Examining the Factors Contributing to Affordable Housing in Kosofe Local Government Council Area, Laogs, Nigeria - M. O, Ajibola; A. O, Oluwunmi; O, Eguh (Journal of Asian Business Strategy, 2012)
The term housing affordability has come into popular usage in the last two decades replacing housing need at the centre of debate about the provision of adequate housing for all. The aim of affordability would be defeated if housing cost becomes burdensome to an individual income in relation to his other needs. This is the reason why the researchers examined the factors contributing to affordable housing in Kosofe Local Government Council Area, Lagos, Nigeria. The study was conducted using questionnaires, administered on randomly selected respondents. A total of 174 copies of the questionnaire were retrieved from the selected respondents in the study area. Both frequency tables and relative importance index (RII) were employed in the analysis of the data collected. The study revealed that the major factors contributing to affordable housing are ease of obtaining finance (RII = 4.48), availability of cheap land (RII = 3.91) and stable economy (RII = 3.84). The study further revealed that the major problems confronting provision of affordable housing in the study area are lack of funds (RII = 3.89), high cost of land (RII = 3.83) and high cost of building materials (RII = 3.30). It is recommended that government should interfere in reducing the cost of land by ensuring equitable marginal distribution of land as well as reduction in the cost of obtaining title to land. It is also recommended that domestic production of building materials should be encouraged so as to increase the construction of houses as well as reduce the cost of construction in the study area.